2018
DOI: 10.4102/safp.v60i6.5014
|View full text |Cite
|
Sign up to set email alerts
|

Challenges experienced by healthcare workers in managing patients with hearing impairment at a primary health care setting: a descriptive case study

Abstract: Background: There has been little research on the experiences of healthcare workers (HCWs) with deaf/hearing impaired (HI) clients. Anecdotal evidence suggests that HCWs experience challenges, but little is reported on how they manage these challenges. Interactions with and care of deaf/Deaf and HI patients by clinicians has yielded several questions around communication and assessment strategies, as well as comparative quality of health care for deaf/Deaf and HI clients. This research was intended to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is consistent with the study of Velonaki et al [6], which indicated that nurses lacked knowledge about Deaf people, suggesting that only 5.8% were aware that Deaf patients were not conversant about their health issues. Supporting these reports, a qualitative report done by Orrie and Motsohi [13] revealed that HCWs had preconceptions and gaps in knowledge and awareness. They identified themes such as language barriers, improvisation and innovation, interpreters, resilience, and recommendations as the point of concern, adding that communication is a challenge, but HCWs claimed this barrier is not insurmountable.…”
Section: Level Of Knowledgementioning
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the study of Velonaki et al [6], which indicated that nurses lacked knowledge about Deaf people, suggesting that only 5.8% were aware that Deaf patients were not conversant about their health issues. Supporting these reports, a qualitative report done by Orrie and Motsohi [13] revealed that HCWs had preconceptions and gaps in knowledge and awareness. They identified themes such as language barriers, improvisation and innovation, interpreters, resilience, and recommendations as the point of concern, adding that communication is a challenge, but HCWs claimed this barrier is not insurmountable.…”
Section: Level Of Knowledgementioning
confidence: 93%
“…Although interpreters help overcome language barriers, inappropriate use of escorts as interpreters may steal patients' independence and confidentiality rights [4]. In the absence of communication assistance, HCWs usually communicate in writing [12], despite knowing the disadvantages of this method, such as patient literacy-level dependency and time consumption [13]. According to one study, only 20% of deaf people have fluency in written English [14].…”
Section: Introductionmentioning
confidence: 99%
“…Inequities and disparities in health care and economics are factors impeding the successful implementation of EHDI programmes in African countries (Engelman 2014;. Inequalities within the African context often disadvantage families in accessing health care, including both structural and procedural access, that is, physical access, funding, transport and communication barriers, as well as attitudes and beliefs of health care providers Orrie & Motsohi 2018). Late-identified hearing impairment poses additional financial stress to the resource-constrained African health care systems, as it is estimated that the cost of severe-profound hearing impairment to society is approximately $300,000 over the lifetime of the hearing-impaired individual (Hear-It.org 2021).…”
Section: Complexities and Challenges With Choice Of Communication The...mentioning
confidence: 99%
“…The authors of this chapter argue for the acknowledgement and incorporation of cultural beliefs and practices, where appropriate, in ECI programmes planning and implementation, particularly because evidence demonstrates that parental beliefs and perceptions influence the outcomes of the therapeutic approach adopted (Majid et al 2017). It is, therefore, important for African audiologists to explore the challenges encountered in the African context while rendering communication interventions with the aim of improving their quality of care and addressing the capacity versus demand challenges so that more children with hearing impairment can have access to evidence-based ECI services (Harmer 1999;Orrie & Motsohi 2018). Chapter 10 comprehensively deliberates on complexities presented by context, particularly linguistic and cultural diversity challenges in preventive audiology in South Africa, with ECI being part of tertiary preventive audiology.…”
Section: Complexities and Challenges With Choice Of Communication The...mentioning
confidence: 99%
“…The authors of this chapter argue for the acknowledgement and incorporation of cultural beliefs and practices, where appropriate, in ECI programmes planning and implementation, particularly because evidence demonstrates that parental beliefs and perceptions influence the outcomes of the therapeutic approach adopted (Majid et al 2017). It is, therefore, important for African audiologists to explore the challenges encountered in the African context while rendering communication interventions with the aim of improving their quality of care and addressing the capacity versus demand challenges so that more children with hearing impairment can have access to evidence-based ECI services (Harmer 1999;Orrie & Motsohi 2018). Chapter 10 comprehensively deliberates on complexities presented by context, particularly linguistic and cultural diversity challenges in preventive audiology in South Africa, with ECI being part of tertiary preventive audiology.…”
Section: Complexities and Challenges With Choice Of Communication The...mentioning
confidence: 99%